The Impact of Group Psychotherapy on the Mental Health of Servicemen with Post-Traumatic Stress Disorder - Motoziuk, Liudmyla; Chorna, Nataliia; Lukashuk, Maryna; Vlasov, Volodymyr; Sobkova, Svitlana (International Journal of Statistics in Medical Research, 2024)
Being in a combat zone negatively affects the psycho-emotional state of servicemen, which can lead to post-traumatic stress disorder (PTSD). The purpose of the study is to determine whether group psychotherapy is effective in reducing symptoms of post-traumatic stress disorder in military personnel. The research methodology is presented by the Post-Traumatic Stress Disorder Checklist for DSM-5, the World Health Organization Quality of Life Instrument, and statistical methods (ANOVA, Levene’s test, and the Mann-Whitney U-test). The results showed that group therapy effectively reduced symptoms of posttraumatic stress disorder from 42.5 (SD = 6.1) to 31.2 (SD = 5.7). The practical significance of the results obtained lies in the possibility of their use in the treatment of post-traumatic stress disorder in military personnel. Prospects for further research lie in studying effective methods of treating other mental disorders in people affected by war.